Structure of a Lys49-Phospholipase A2 homologue isolated from the venom of Bothrops nummifer (jumping viper) - de Azevedo, Walter Filgueira (1999)
Lys49-Phospholipase A2 (Lys49-PLA2) homologues damage membranes by a Ca2+-independent mechanism which does not involve catalytic activity. We have solved the structure of myotoxin-I, a Lys49-PLA2 homologue isolated from the venom of Bothrops nummifer (jumping viper) at 2.4 A resolution using molecular replacement techniques. The final model has been refined to a final R-factor of 18.4% (R-free = 23.2%), and shows excellent geometry. The myotoxin-I from Bothrops nummifer is dimeric in the crystalline state as has been observed for other Lys49-PLA2 homologues. In addition, a continuous electron density in the active site and substrate binding channel could be successfully modeled as a fatty-acid molecule.